Open-end design - Henriksson, Josefin (2014)

(untitled)
As harbours all over the world are being modernised and converted into non-industrial areas. Many older port areas have been subjected to tabula rasa transformations that erases the sites specific qualities and ignores their context in the urban fabric. Often the result is revealed to be an international, standardised design, with little regard to the site itself. It is a development that make these areas look almost identical no matter where they are found.